х = 10
Пошаговое объяснение:
2х - х = 20 - 10
х = 10
проверяем 10 - 10 = 20 - (10 * 2)
10 - 10 = 20 - 20
0 = 0
В решении.
Пошаговое объяснение:
2) Решите неравенство:
а) 6+х < 3 - 2х ;
х + 2х < 3 - 6
3x < -3
x < -1
Решение неравенства х∈(-∞; -1).
б) 7-4х < 6х-23;
-4х - 6х < -23 - 7
-10x < -30
10x > 30 (знак неравенства меняется при делении на -1)
x > 30/10
x > 3
Решение неравенства х∈(3; +∞).
в) 2(3+х) - (4-5х) ≤ 9;
6 + 2x - 4 + 5x <= 9
7x + 2 <= 9
7x <= 9 - 2
7x <= 7
x <= 1
Решение неравенства х∈(-∞; 1].
г) 0,8(х-3) - 3,2 ≤ 0,3(2 - х)
0,8x - 2,4 - 3,2 <= 0,6 - 0,3x
0,8x - 5,6 <= 0,6 - 0,3x
0,8x + 0,3x <= 0,6 + 5,6
1,1x <= 6,2
x <= 6,2/1,1
x <= 62/11 (5 и 7/11)
Решение неравенства х∈(-∞; 62/11].
10-10=0
20-(10×2)=0 10×2=20 20-20=0
x=10